2021
DOI: 10.1038/s41467-020-20332-8
|View full text |Cite
|
Sign up to set email alerts
|

Two novel venom proteins underlie divergent parasitic strategies between a generalist and a specialist parasite

Abstract: Parasitoids are ubiquitous in natural ecosystems. Parasitic strategies are highly diverse among parasitoid species, yet their underlying genetic bases are poorly understood. Here, we focus on the divergent adaptation of a specialist and a generalist drosophilid parasitoids. We find that a novel protein (Lar) enables active immune suppression by lysing the host lymph glands, eventually leading to successful parasitism by the generalist. Meanwhile, another novel protein (Warm) contributes to a passive strategy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 103 publications
0
70
0
Order By: Relevance
“…how to synchronise development with the host and how to combat with the host immune system. Correspondingly, a related study showed that the more powerful active immune suppression, which is absent in the specialist, allows broad parasitisation in the generalist Lh 34 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…how to synchronise development with the host and how to combat with the host immune system. Correspondingly, a related study showed that the more powerful active immune suppression, which is absent in the specialist, allows broad parasitisation in the generalist Lh 34 .…”
Section: Discussionmentioning
confidence: 90%
“…Both strains were checked with Lb filamentous virus (LbFV) by mapping whole-genome sequencing reads with the virus reference. Genome sequencing reads of Lb is the sequencing data for polishing the assembly of long reads (see below), and the reads of Lh was generated by the previous study 34 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lb infection activates many components of humoral and cellular immunity: Toll-NF-κB, JAK-STAT, and the melanization pathways and their target genes are transcriptionally upregulated; there is a burst of hematopoietic proliferation and differentiation of blood cells (also called hemocytes) in the lymph gland and in circulation. If the immune responses are strong and sustained, macrophages and lamellocytes encapsulate and kill wasp eggs [7][8][9][10][11]. Lh infection in contrast suppresses immune gene expression and kills immature and mature larval hemocytes [12,13].…”
Section: Introductionmentioning
confidence: 99%